DETERMINATION THE SOCIAL MEDIA EFFECTIVENESS LEVEL OF UNIVERSITIES IN TURKEY (Third Sector Social Economic Review, 2018)
Intense use of social media by individuals has made it inevitable for institutions to take part in social media. Universities have started to use social media effectively to reach their target groups and publicize their services. This study aims to determine whether there is a significant relationship between the number of students and social media effectiveness levels of state and foundation universities. The basic assumption of the study is both state and foundation universities in Turkey have a significant correlation between the number of university students and social media effectiveness level. The hypotheses developed within the framework of the purpose and basic assumption of the study were tested with Pearson Correlation and Regression Analysis. The study carries a unique value determininig both state and foundation universitiesthe social media effectiveness level and correlation between student number and social media effectiveness level.
Keywords: Social Media; Facebook; Twitter; Instagram; University